Isoxazole-tethered diarylheptanoid analogs: Discovery of a new drug-like PAR2 antagonist. Issue 13 (15th July 2018) - Bhuniya, Debnath; Bhosale, Sandeep; Reddy, Satyanarayana B.; Reddy, Sudharshan N.
Graphical abstract: Highlights: Design of a new class of isoxazole-tethered diarylheptanoid analogs. Stereo-conserved access to syn and anti -1, 3-diol features starting from d -glucose. Significantly improved in vitro drug-like properties compared to curcumin-I. Structurally distinct and phytochemical based PAR2 antagonist scaffold. Highlighted analog 4a with PAR2 IC50 : 6 μM (HEK293 cells, trypsin agonist). Abstract: A new class of isoxazole-tethered diarylheptanoids having characteristic 1, 3- syn -diol and 1, 3- anti -diol chemophoric moieties, e.g. 4a –d and 5a –c respectively, have been designed and synthesized starting from d -glucose following a stereo-conserved general synthetic strategy. The isoxazole heterocycle was installed using our recently elaborated methodology deploying Magtrieve™ as a selective oxidizing agent. Two of these new analogs 4a and 5a exhibited significantly improved in vitro drug-like properties including solubility, metabolic stability, cell permeability and lack of nonspecific cytotoxicity when compared with curcumin-I. In a HEK293 cell-based intracellular calcium [Ca 2+ ]i release assay, 4a and 5a, when tested at 30 μM, inhibited the trypsin agonist induced protease-activated receptor-2 (PAR2) activity by 80% and 70% respectively. IC50 of 4a (SB70) has been determined as 6 μM which is in the same range of current benchmarks for PAR2 antagonists.